MMP3 Is a Non-invasive Biomarker of Rejection in Skin-Bearing Vascularized Composite Allotransplantation: A Multicenter Validation Study - Kollar, Branislav; Uffing, Audrey; Borges, Thiago J.; Shubin, Andrey V.; Aoyama, Bruno T.; Dagot, Céline; Haug, Valentin; Kauke, Martin; Safi, Ali-Farid; Talbot, Simon G.; Morelon, Emmanuel; Dakpe, Stéphanie; et al. (Frontiers in Immunology, 2019)
Background: There is unmet need for non-invasive immunomonitoring to improve diagnosis and treatment of acute rejection in vascularized composite allotransplantation (VCA). Circulating matrix metalloproteinase 3 (MMP3) was described as a candidate non-invasive biomarker to predict treatment response to acute rejection in clinical VCA. However, larger validation studies are yet to be reported to allow for more definitive conclusions. Methods: We retrospectively measured MMP3 levels using ELISA in a total of 140 longitudinal serum samples from six internal and three external face transplant recipients, as well as three internal and seven external upper extremity transplant recipients. The control groups comprised serum samples from 36 kidney transplant recipients, 14 healthy controls, and 38 patients with autoimmune skin disease. A linear mixed model was used to study the effect of rejection state (pre-transplant, no-rejection, non-severe rejection (NSR), and severe rejection) on MMP3 levels. Results: In VCA, MMP3 levels increased significantly (p < 0.001) between pre- and post-transplant no-rejection states. A further increase occurred during severe rejection (p < 0.001), while there was no difference in MMP3 levels between non-severe and no-rejection episodes. A threshold of 5-fold increase from pre-transplant levels could discriminate severe from NSR with 76% sensitivity and 81% specificity (AUC = 0.79, 95% CI = 0.65–0.92, p < 0.001). In kidney transplantation, the MMP3 levels were significantly (p < 0.001) elevated during antibody-mediated rejection but not during T-cell mediated rejection (TCMR) (p = 0.547). MMP3 levels in healthy controls and autoimmune skin disease patients were comparable with either pre-transplant or no-rejection/NSR episodes of VCA patients. Conclusion: The results of this study suggest that serum MMP3 protein is a promising marker for stratifying patients according to severity of rejection, complementary to biopsy findings.